Circulating Monocytes Are Not a Major Reservoir of HIV-1 in Elite Suppressors - Spivak, Adam M. (American Society for Microbiology, 2011)
Circulating HIV-1-infected monocytes have been identified in patients on highly active antiretroviral therapy and may represent an important barrier to viral eradication. The nature of these cells in HIV-1-infected patients who maintain undetectable viral loads and preserved CD4(+) T cell counts without antiretroviral therapy (known as elite controllers or elite suppressors [ES]) is unknown. We describe here infrequent recovery of proviral HIV-1 DNA from circulating monocytes relative to CD4(+) T cells in ES, despite permissiveness of these cells to HIV-1 viral entry ex vivo. Thus, monocytes do not appear to be a major reservoir of HIV-1 in ES.